2004
DOI: 10.1002/ejic.200400034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure Determination and Cytotoxicity of the PdII·Bleomycin A2 Complex

Abstract: The solution structure of the Pd II ·bleomycin A2 complex was resolved by NMR spectroscopy in combination with molecular modelling. The preparation of the complex in 1.0 M NaCl aqueous solutions leads to the formation of a major compound, which is very stable at ambient temperature. Our NMR spectroscopic data demonstrate that bleomycin is coordinated through the β-aminoalanine secondary amine, the pyrimidine ring N1, the deprotonated histidyl amide and the imidazole N1, in contrast to an earlier study that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…BLM provides five or six ligands for binding to the iron. Because no crystal structure exists, current knowledge of the Fe−BLM structure is based on spectroscopy, molecular dynamics modeling, density functional calculations, , and studies on BLM complexes with Co, Cu, , and other metals. All studies agree on five nitrogen-based ligands (indicated in bold in Figure ). The four equatorial ligands are generally accepted to be an imidazole nitrogen, a deprotonated amide, a pyrimidine nitrogen, and the secondary amine functionality of the β-aminoalanine.…”
Section: Introductionmentioning
confidence: 99%
“…BLM provides five or six ligands for binding to the iron. Because no crystal structure exists, current knowledge of the Fe−BLM structure is based on spectroscopy, molecular dynamics modeling, density functional calculations, , and studies on BLM complexes with Co, Cu, , and other metals. All studies agree on five nitrogen-based ligands (indicated in bold in Figure ). The four equatorial ligands are generally accepted to be an imidazole nitrogen, a deprotonated amide, a pyrimidine nitrogen, and the secondary amine functionality of the β-aminoalanine.…”
Section: Introductionmentioning
confidence: 99%